How does vertical reading affect saccade programming and lexical processing in the Roman script? - Özkan, Zeynep G.; Hyönä, Jukka; Fernández-López, Maria; Perea, Manuel (Springer Nature, 2026)
Although computational models of eye movement control in reading have focused on horizontal text layouts, vertically oriented text is also encountered in daily life in the Roman script. To examine the interplay between saccade programming and lexical processing under vertical reading in the Roman script, we manipulated (1) the layout of words in a sentence (horizontal vs. vertical) and (2) word frequency (high vs. low). In the vertical layout, the words themselves remained in standard orientation but were arranged vertically (one below the other). Eye-movement measures at the sentence level (e.g., total reading time, number of fixations) showed a cost for the vertical arrangement, primarily reflected in longer fixation durations rather than a greater number of fixations. Critically, at the target-word level, the word-frequency effect —which increased in later eye-fixation measures (gaze duration, total time)— remained similar in size across both layouts. The additive pattern of word frequency and text layout, supported by Bayes factors, suggests that slower saccade programming in the vertical format does not substantially impact lexical processing. While lexical processing can influence saccade programming, delays in saccade programming do not, in turn, alter lexical processing—a pattern that constrains current models of eye movement control in reading.